The Feasibility of Whole-body In Vivo X-ray Fluorescence of Lead in Bone in Mice - Cheung, Tsz Wing (My University, 2018)
Previous studies have shown an association between Pb exposure and intelligence quotient (IQ). Up until now, there is a lack of technology and methodology to assess the effects of long-term Pb exposure (such as de-myelination) in brain in-vivo. So we are developing a mouse model that will allow us to assess in vivo Pb in bone and brain structure and myelination using magnetic resonance imaging (MRI). In this project, we will discuss the feasibility of an in vivo x-ray fluorescence (XRF) system for the Pb measurement in the skeleton of whole mice. A review of literature is conducted in chapter 1. Health impacts of lead, measurement of lead, pre-existing bone Pb phantoms and mouse model selection are explained thoroughly. In chapter 2, calibration and minimum detection limits (MDLs) for the XRF measurements are documented. Calibration was performed using Plaster of Paris phantoms mimicking human bone doped with Pb concentrations ranging from 0 to 100 ppm. Detection limits for the pre-existing bone Pb phantoms were found to be 1.52 μg Pb/g plaster for 1-hour measurement. For 2 strains of Pb free mice (CD-1 and C57BL/6J), which had skull and hind facing detectors respectively, MDLs of 5.66 – 7.78 μg Pb/g and 6.69 – 8.50 μg Pb/g were determined for 3-hour measurement. This detectability of MDLs by the XRF system encourages us to proceed to measure mouse-mimicking phantoms. In order to evaluate the feasibility of a 109Cd XRF system for the Pb measurement in the skeleton of whole mice, mouse-mimicking phantoms were made and measured. The effect of variations in Pb distribution across the mouse and the applicability of the normalization in mice are discussed in chapter 3. To sum up, our system can measure Pb in whole mice in vivo at the levels of Pb in bone that are anticipated in brain de-myelination studies. Our results indicate that if multiple orientations (rotated) are measured in mice, the mean bone Pb level in whole mice will be determined accurately.
Keywords: XRF; X-ray fluorescence; Lead; Lead in bone; Minimum detection limit; Mouse-mimicking phantoms; Mean bone Pb level